Embodied Arabic Orthography through Rasm ‘Uthmānī Copybook Practice: A Mixed-Methods Study in Malaysia - Yusuf Arisandi; M. Yusuf Harun; Aufa Hanin Salsabil (Institut Agama Islam Negeri Curup, 2026)
Arabic writing skills (mahārah kitābah) remain a persistent challenge in Islamic educational contexts, where instruction often emphasizes memorization and oral recitation while providing limited structured support for handwriting development. Although learners are frequently exposed to Qur’anic texts, such exposure does not automatically lead to accurate and confident Arabic writing. This study examines the implementation and pedagogical impact of Rasm ‘Uthmānī Qur’anic copybook practice on Arabic writing development among beginner and lower-intermediate learners in Negeri Sembilan, Malaysia. Employing a qualitative-dominant convergent mixed-methods design, the study involved 32 students who participated in a six-week copybook-based writing intervention. Data were collected through classroom observations, semi-structured interviews, analysis of students’ written artifacts, and pre- and post-writing performance assessments. Qualitative data were analyzed thematically through coding, categorization, and interpretive synthesis, while quantitative data were analyzed using descriptive statistics and a paired-samples t-test. The findings indicate that copybook-based practice improved orthographic accuracy, letter formation, baseline alignment, and writing consistency, while also reducing writing anxiety and enhancing learner confidence. The faint-script tracing format served as visual–motor scaffolding, supporting psychomotor learning, gradual automatization, and affective readiness for writing. The study concludes that Rasm ‘Uthmānī Qur’anic copybooks can serve as a culturally authentic pedagogical medium for integrating Qur’anic literacy with Arabic writing instruction and for developing mahārah kitābah in Islamic educational settings.